Roads Assessment for Wind Turbines Transfer to Maysan Provence - Iraq - Shaban, Auday H. (Iraqi Journal of Science, 2022)
Wind farm assessment project have several steps. This paper aim on the second step which is harvesting the roads properties from the loading point to the construction point. The difficulties of examining the roads whether they are appropriate or not for transporting wind turbine components. The selected site for establishing wind farm is located at Maysan province and has 262 km distance from Um – Qaser port. The results through applying remote sensing and GIS techniques on Landsat (30 m resolution) and QuckBird (0.6 m resolution) are summarized by (2 hard turn, 18 Bridges that crossing over, and 13 Bridges passing under).